If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(-7) = 12 Multiply -1 * -7 5 + 7 = 12 Combine like terms: 5 + 7 = 12 12 = 12 Add '-12' to each side of the equation. 12 + -12 = 12 + -12 Combine like terms: 12 + -12 = 0 0 = 12 + -12 Combine like terms: 12 + -12 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5(w+12)= | | 4x-5+3x=9 | | 4q=7q+37 | | 1.5-0.25(a+4)=3+(.05-0.5a) | | 4t^2+18t-400=0 | | -20=-7x+1 | | 5(-4x-3)=13x+9 | | -50-7x=-3x+62 | | 312x+51=33 | | 4c-7=3c | | 9x+10y=-16 | | 9y-15=-2(y-6) | | 34+5n=9 | | 20-2n=80 | | 3d-4(5d-8)=-12-6d | | 2x+(2x-1)=31 | | 5x+7+3x=-1 | | 8(x+2)=-6(x+5) | | (2x+9)(4x+2)= | | 15m+3m=-18 | | 12y=3(4y-7) | | 10b-9b=2 | | 4-2(3X-2)=2(X-3) | | 8v+12=4(2v+3) | | 2+x*3+2x=21 | | 8x^2+-14x+3=0 | | 1.3p+1=1.6 | | 3x-2x+1=5 | | 62=x-6x+2 | | 7=1x(3+2x) | | -8+4x+4x=-88 | | 2(4x-3)-7(x+1)= |